Barleriside A, an aryl hydrocarbon receptor antagonist, ameliorates podocyte injury through inhibiting oxidative stress and inflammation - Li, Xiao-Jun; Wang, Yan-Ni; Wang, Wen-Feng; Nie, Xiaoli; Miao, Hua; Zhao, Ying-Yong (Frontiers in Pharmacology, 2024)
Increasing evidence shows that hyperactive aryl hydrocarbon receptor (AHR) signalling is involved in renal disease. However, no currently available intervention strategy is effective in halting disease progression by targeting the AHR signalling. Our previous study showed that barleriside A (BSA), a major component of Plantaginis semen, exhibits renoprotective effects. In this study, we determined the effects of BSA on AHR expression in 5/6 nephrectomized (NX) rats. We further determined the effect of BSA on AHR, nuclear factor kappa B (NF-ƙB), and the nuclear factor erythroid 2-related factor 2 (Nrf2) signalling cascade in zymosan-activated serum (ZAS)-stimulated MPC5 cells. The results showed that BSA treatment improved renal function and inhibited intrarenal nuclear AHR protein expression in NX-treated rats. BSA mitigated podocyte lesions and suppressed AHR mRNA and protein expression in ZAS-stimulated MPC5 cells. BSA inhibited inflammation by improving the NF-ƙB and Nrf2 pathways in ZAS-stimulated MPC5 cells. However, BSA did not markedly upregulate the expression of podocyte-specific proteins in the ZAS-mediated MPC5 cells treated with CH223191 or AHR siRNA compared to untreated ZAS-induced MPC5 cells. Similarly, the inhibitory effects of BSA on nuclear NF-ƙB p65, Nrf2, and AHR, as well as cytoplasmic cyclooxygenase-2, heme oxygenase-1, and AHR, were partially abolished in ZAS-induced MPC5 cells treated with CH223191 or AHRsiRNA compared with untreated ZAS-induced MPC5 cells. These results indicated that BSA attenuated the inflammatory response, partly by inhibiting AHR signalling. Taken together, both pharmacological and siNRA findings suggested that BSA mitigated podocyte lesions by improving the NF-ƙB and Nrf2 pathways via inhibiting AHR signalling. Therefore, BSA is a high-affinity AHR antagonist that abolishes oxidative stress and inflammation.